PSVII-5 Soil parameters affect ammonia fluxes from livestock urine and urea fertilizer. (5th December 2019) - Longhini, Vanessa Z; Cardoso, Abmael S; Berça, Andressa S; Gonçalves, Pedro H; Boddey, Robert M; Reis, Ricardo; Dubeux, Jose C B; Ruggieri, Ana Claudia
Abstract: This study evaluated soil parameters involved in ammonia (NH3 ) fluxes from livestock excreta and urea fertilizer. Treatments were distributed in a randomized block design, with five replicates. Treatments included application of 1) urine; 2) dung; or 3) urea fertilizer (50 kg N ha -1 ) on palisadegrass pasture (Brachiaria brizantha cv. Marandu). Excreta was collected from crossbred heifers grazing palisadegrass pastures. One soil background treatment without excreta or urea was included for the measurement of NH3 fluxes. Treatments were applied in May/2017, April/2018, and Jul/2018. One liter of urine, 1.6 kg of dung, and 2.67 g of urea fertilizer were added inside the chamber according to treatment. Ammonia flux was evaluated using a semi-opened free static chamber and N determination by steam distillation. The extracted solution of fresh soil was analyzed in spectrophotometer. Pearson's correlation and linear regression analyses were run to identify which soil parameters explained NH3 ﬂuxes. Soil parameters were ammonium (NH4 + ), nitrate (NO3 - ), pH, and water filled pore space (%WFPS). For urine, a negative correlation (r = -0.68; P = 0.005) was found between NH3 flux and NO3 - . Soil NO3 - and pH affected NH3 fluxes as determined by multivariate regressions analysis. For urea fertilizer, a positive correlation was found between NH3 flux and NH4 + (r=0.62; P = 0.03), NH3 flux and NO3- (r = 0.57; P = 0.03), and NH3 flux and %WFPS (r = 0.59; P = 0.02). The %WFPS affected NH3 fluxes as determined by single regressions analysis. There was no significant correlation between NH3 fluxes and the soil parameters (P > 0.05) when dung was applied. Greatest N loss by NH3 emission when urine was applied decreased soil NO3 - . Dung formed a superficial crust that might have acted as a physical barrier, reducing losses. Greater soil moisture increased urea hydrolysis resulting in soil ammonification and nitrification. Nitrates for urine and %WFPS for urea were the major drivers affecting NH3 fluxes.